Association of serum lipid components and obesity with genetic ancestry in an admixed population of elderly women - Lins, Tulio Cesar de Lima (2012)
The prevalence of metabolic disorders varies among ethnic populations and these disorders represent a critical health care issue for elderly women. This study investigated the correlation between genetic ancestry and body composition, metabolic traits and clinical status in a sample of elderly women. Clinical, nutritional and anthropometric data were collected from 176 volunteers. Genetic ancestry was estimated using 23 ancestry-informative markers. Pearsons correlation test was used to examine the relationship between continuous variables and an independent samples t-test was used to compare the means of continuous traits within categorical variables. Overall ancestry was a combination of European (57.49%), Native American (25.78%) and African (16.73%). Significant correlations were found for European ancestry with body mass index (r = 0.165; p = 0.037) and obesity (mean difference (MD) = 5.3%; p = 0.042). African ancestry showed a significant correlation with LDL (r = 0.159, p = 0.035), VLDL (r = -0.185; p = 0.014), hypertriglyceridemia (MD = 6.4%; p = 0.003) and hyperlipidemia (MD = 4.8%; p = 0.026). Amerindian ancestry showed a significant correlation with triglyceride levels (r = 0.150; p = 0.047) and hypertriglyceridemia (MD = 4.5%; p = 0.039). These findings suggest that genetic admixture may influence the etiology of lipid metabolism-related diseases and obesity in elderly women.